The Effect of CSR on Company Value with Profitability as a Moderation Variable in the Private Bank Sector on the IDX for the 2021–2023 Period - Farkhana Farkhana; Resha Geofany Heryana; Ario Pordianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to assess how Corporate Social Responsibility (CSR) impacts increasing company value, as well as exploring whether the level of profitability can strengthen these relationships. This study focuses on private banks listed on the Indonesia Stock Exchange (IDX) in the period from 2021 to 2023. The method used is quantitative with an interaction regression analysis approach (moderation), and the data processing process is carried out using IBM SPSS software version 22. CSR is measured through the ratio between funds allocated to social activities and overall operational expenses. Meanwhile, the company's value is represented by the Price to Book Value (PBV) ratio, and profitability is proxied by the Return on Assets (ROA). The results of the study show that separately, CSR and ROA do not have a significant impact on the company's value. However, when the two are combined, the influence is significant, indicating that profitability is able to strengthen the role of CSR in increasing company value.